GC-MS analysis of volatile components in different populations of Ophiocordyceps sinensis: GC-MS volatile components in O. sinensis - Jinna, Zhou; Khan, Tahir; Haiwen, Xia; Jinlin, Liu; Zhenji, Wang (Cellular and Molecular Biology, 2025)
Cordyceps, a genus of ascomycete fungi, are renowned for their medicinal and functional food applications, and are attributed to bioactive compounds such as nucleosides, lipids, saccharides, and amino acids. Among its species, Ophiocordyceps sinensis has significant pharmacological value, impacting multiple organ systems and exhibiting antioxidant and antitumor properties. Although natural populations are limited, artificial cultivation has provided a sustainable source of medicinal products. This study investigated the volatile components of O. sinensis mycelia from five regions, Tibet, Yunnan, Sichuan, Gansu, and Qinghai, using gas chromatography-mass spectrometry (GC-MS) combined with multivariate statistical analysis. Fifty volatile substances were identified, including hydrocarbons, acids, esters, alcohols, phenols, aldehydes, and ketones, with hydrocarbons being the most abundant (60%). Cluster analysis highlighted significant differences in the volatile profiles between populations, with 12 common compounds identified across all regions. Population-specific variations in volatile classes, such as hydrocarbons, acids, and alcohols, were observed, suggesting a composite odor profile for O. sinensis rather than a single characteristic scent. This study provides insights into the chemical diversity of volatile components in O. sinensis, emphasizing the influence of climatic factors and advancing their potential applications in medicinal and functional products.